Levels of Disagreement Over Contested Practices - Silva, Eric O. (Qualitative Sociology Review, 2013)
This article unravels the tangled threads of argumentation that can be found in public debate over institutional practices. An analysis of letters to the editor (n=1551) written about two contested practices (American Indian mascots and the exclusive teaching of evolutionary theory) uncovers three analytically distinct levels of disagreement in the discourse. In the first level, partisans debate the effects of keeping or eliminating the contested practice. This disagreement over consequences leads to a second disagreement over how the social criteria for adjudicating controversies apply to the situation. This application level sits atop a third foundational level of the discourse where partisans debate the nature of social reality and the definition of the rules.